Formulasi Strategi Pemasaran Lembaga Amil Zakat Nasional Yayasan Yatim Mandiri - Wardojo, Bimo Wahju (JURNAL AKUNTANSI DAN MANAJEMEN, 2020)
In the past five years (2014-2018) LAZNAS Yatim Mandiri experienced: (1) the growth rate of LAZNAS Yatim Mandiri donation growth decreased from two digits to only one digit; (2) declining market share of LAZNAS Yatim Mandiri donations; (3) the low growth rate of LAZNAS Yatim Mandiri donation collection in the last five years has been 8% compared to the average growth rate of zakat nationally (25.79%) This study aims to design the right marketing strategy formulation for LAZNAS Yatim Mandiri to increase market share in the competitive era by using diamond strategy frame work. The research method used in research is a qualitative approach, namely case studies. Data collection uses literature study and in-depth interviews. The results of this study recommend the marketing strategy formulation based on the diamond strategy framework including arenas, vehicles, differentiators, staging and ecolonomic logic